Oxazole and isoxazole: From one-pot synthesis to medical applications. (30th July 2022) - Thakur, Ajay; Verma, Monika; Bharti, Ruchi; Sharma, Renu
Abstract: N, O -containing five-membered heterocycles especially oxazole and isoxazole, have widely been found in many natural products and drugs with relevant medicinal and pharmaceutical applications. Because of their exhaustive bioactivities, the development of new synthetic routes always remains a center of attraction between researchers and scientists. In this direction, one pot synthesis have been proven as one of the efficient and green approach for the synthesis of these bioactive heterocycles. The influential nature of this methodology has been well established in drug discovery, catalysis, pharmaceutical, and combinatorial chemistry. The development of multicomponent reactions leading to oxazole/isoxazoles has expanded rapidly over the last decades. Despite their myriad applications, no detailed report has been made on the recent literature of oxazole/isoxazole derivatives. This review article aims to cover the journey of one-pot reactions to oxazole/isoxazoles, including the synthetic strategies scope, reaction conditions rationale behind the choice of catalyst and solvents, along with their medicinal applications. Graphical abstract: Image 1